Audiovisual Manual for Scientific Training - Llinás, Diego; Caballero, María José; Andrada, Marisa (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article presents a review of the need and general situation of audiovisual support for training in the scientific technical university field in all Spanish public universities, contextualized in the growing demand for digitization, because of the continuous acceleration of training activity online. In relation to this situation, the results of the application of a Network Production Model (audiovisual) developed in the past, as support for the need for Scientific Dissemination, presenting an example of its updating to produce didactic material for university internships, both face-to-face and online.